2019
DOI: 10.21577/0103-5053.20190006
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Determination by Direct Infusion ESI-MS and Fatty Acid Composition by GC-FID in Human Milk Pools by Folch and Creamatocrit Methods

Abstract: Human milk (HM) is extremely important to the baby, containing a varied and balanced range of nutrients fundamental to the ideal development of the newborn. Among these nutrients, HM lipids provide 40-60% of the energy. In HM banks, the creamatocrit method is employed as a quick and solvent-free tool, however, since Folch methodology is considered reference for lipid extraction, this study compared the fatty acid (FA) composition and the lipid profile by gas chromatography with flame ionization detector (GC-FI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
2
4
0
2
Order By: Relevance
“…Research, Society and Development, v. 9, n. 12, e26891211136, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.11136 Comparing the results obtained by the composition in FAs (Tables 3, 4 and 5) with the estimates of TAGs presented in Table 6, it was possible to observe the high frequency of combinations of oleic acid (O, 18:1n-9), palmitic acid ( P, 16:0) and linoleic acid (L, 18:2n-6) in these TAGs. These results were similar to the work by Manin et al (2019) In a study by Haddad et al (2011), in which the composition of molecular TAG species in mature milk was analyzed, the POO species (13.587%), PLO (3.045%), POP (9.790%) also stood out. Despite the intensity found in this work for PLO to be lower and for POP to be higher than those found in our study, it is noted that these species of TAGs were predominant, in addition to LaPO, MPO and PLL, which represented approximately 50% of the total of TAGs.…”
Section: Determination Of Triacylglycerol By Esi(+)-mssupporting
confidence: 91%
See 3 more Smart Citations
“…Research, Society and Development, v. 9, n. 12, e26891211136, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.11136 Comparing the results obtained by the composition in FAs (Tables 3, 4 and 5) with the estimates of TAGs presented in Table 6, it was possible to observe the high frequency of combinations of oleic acid (O, 18:1n-9), palmitic acid ( P, 16:0) and linoleic acid (L, 18:2n-6) in these TAGs. These results were similar to the work by Manin et al (2019) In a study by Haddad et al (2011), in which the composition of molecular TAG species in mature milk was analyzed, the POO species (13.587%), PLO (3.045%), POP (9.790%) also stood out. Despite the intensity found in this work for PLO to be lower and for POP to be higher than those found in our study, it is noted that these species of TAGs were predominant, in addition to LaPO, MPO and PLL, which represented approximately 50% of the total of TAGs.…”
Section: Determination Of Triacylglycerol By Esi(+)-mssupporting
confidence: 91%
“…Our results were approximate results to the work of Silva et al (2005) and Lubetzky et al (2016), who studied the composition in HM FAs of Brazilian lactating mothers and obtained concentrations of PUFAs,MUFAs and SFAs of 23.04,27.60 and 39.70%,and 20.6,38.0 and 43.0%,respectively. Regarding MUFAs,) from the omega-6 family and α-linolenic acid (18:3n-3) from the omega-3 family are considered essential FAs, that is, they need to be purchased from the feeding, the evaluated HMs presented values between 17.29 to 18.51%, and 0.93 to 1.09%, respectively, values similar to other studies found in the literature (Kuipers et al, 2012;Manin et al, 2019). These MUFAs have important functions, especially in early life, where growth is intense, in addition to helping to form the immune system and the central nervous system.…”
Section: Fatty Acid Composition By Gc-fidsupporting
confidence: 81%
See 2 more Smart Citations
“…Other publications show ten times higher NA content in colostrum compared to mature milk [11,12]. However, there are also a few publications that report the NA concentrations decrease from 0.35 to 0.27 mg/g of human milk, with no significant difference between colostrum and mature milk [36].…”
Section: Discussionmentioning
confidence: 99%